Menarche age and its association with BMI and socioeconomic status among some school girls in Tikrit City (Tikrit Journal of Pharmaceutical Sciences, 2023)
Body mass index (BMI) is useful for categorizing  under- and over-nutrition. It is the weight in kilogram divided by the height in meters and squared. Socioeconomic status (SES) is an economic and sociological combined total measure of a person's work experience and of an individual's or family's economic access to resources and social position in relation to others.Menarche is defined as the first menstrual period in a female adolescent. The purpose of this study to find out the effect of BMI and socioeconomic state on menarche among school girls in Tikrit. Methodology : In this study 100 female, aging 11-13 years old  were selected in Al-Marjan secondary school of Tikrit region. Height and weight were measured. The body mass index (BMI; kg/m2) was used as an index of relative weight. The socioeconomic status were assessed according to the educational and occupational levels of parents of the girls. The age at menarche were evaluated . This study was done from December 2021 to March 2022. Results : The mean and standard deviation (SD) of menarche age was 12.87 ± 1.17 years. About 60.3% of girls had normal BMI and 31%, 6.8%, and 2% of them were underweight, overweight, and obese, respectively. There was no significant relationship between higher BMI and menarche age. There was no significant relationship between socioeconomic status, physical activity, and birth season, attitude towards menarche, nutritional status, and number of brothers with age of menarche .While there was a significant association of number of sisters and the menarche age. Conclusions: The results showed a no significant relationship between menarche age and BMI. The age of menarche in this region was also different compared to other regions of the globe.